Highly efficient perovskite solar cells for light harvesting under indoor illumination via solution processed SnO2/MgO composite electron transport layers. (July 2018) - Dagar, Janardan; Castro-Hermosa, Sergio; Lucarelli, Giulia; Cacialli, Franco; Brown, Thomas M.
Abstract: We present new architectures in CH3 NH3 PbI3 based planar perovskite solar cells incorporating solution processed SnO2 /MgO composite electron transport layers that show the highest power outputs ever reported for photovoltaic cells under typical 200–400 lx indoor illumination conditions. When measured under white OSRAM LED lamp (200, 400 lx), the maximum power density values were 20.2 µW/cm 2 (estimated power conversion efficiency, PCE = 25.0%) at 200 lx and 41.6 µW/cm 2 (PCE = 26.9%) at 400 lx which correspond to a ∼ 20% increment compared to solar cells with a SnO2 layer only (even at standard 1 sun illumination, where the maximum PCE was 19.0%). The thin MgO overlayer leads to more uniform films, reduces interfacial carrier recombination, and leads to better stability. All layers of the cells, except for the two electrodes, are solution processed at low temperatures for low cost processing. Furthermore, ambient indoor conditions represent a milder environment compared to stringent outdoor conditions for a technology that is still looking for a commercial outlet also due to stability concerns. The unparalleled performance here demonstrated, paves the way for perovskite solar cells to contribute strongly to the powering of the indoor electronics of the future (e.g. smart autonomous indoor wireless sensor networks, internet of things etc). Graphical abstract: fx1 Highlights: Perovskite solar cells incorporating new solution-processed SnO2 /MgO composite ETLs. The thin MgO overlayer enhances efficiency by 20%, reducing charge recombination. Maximum PCE of 19.0% under 1 sun illumination with a stabilized value of 18.1%. Maximum power density: 20.2 µW/cm 2 at 200 lx; 41.6 µW/cm 2 at 400 lx (PCE = 26.9%). Highest power outputs ever reported under typical 200–400 lx indoor illumination.